Plasmonic Structures for Near Infrared Applications. Issue 1629 (22nd January 2014) - Floris, Francesco; Marabelli, Franco; Patrini, Maddalena; Fornasari, Lucia; Quochi, Francesco; Figus, Cristiana; Bongiovanni, Giovanni; Mura, Andrea; Saba, Michele; Pellecani, Paola; Valsesia, Andrea
ABSTRACT: We report on the development of a plasmonic-photonic coupled platform based on a plasmonic periodic nanostructure and a host matrix for active media in the visible-near infrared range, constituted by a thin film of sol-gel glass. Here, we report on preliminary results about two main tasks of the research work. On one side, we have studied and optimized the surface that supports plasmonic resonances with tunable wavelengths. On the other side, we focused on improving the sol-gel techniques to form and deposit thin films appropriate for covering the previous surface as well as to protect it (i.e. for sensing applications), embed suitable fluorophores (for active device applications) while avoiding metal-induced radiative emission quenching. Besides structural and optical characterization of the considered structures and films, finite-difference time-domain numerical simulations have been performed, in order to give a feedback on the structure features and thereby interpret its optical response.